Percutaneous and surgical treatment of mitral valve regurgitation - Seeburger, Joerg; Katus, Hugo; Pleger, Sven Torsten; Krumsdorf, Ulrike; Mohr, Friedrich W.; Bekeredjian, Raffi (Deutsches Ärzteblatt, 2011)
Diseases of the mitral valve are the second-most common clinically significant form of valvular defect in adults. Mitral valve regurgitation in particular occurs with increasing frequency as part of degenerative changes in the course of aging. The...
Gesehen am 31.10.2022